SCREENING AND ISOLATION OF INTRACELLULAR α- GALACTOSIDASE PRODUCING MICROORGANISMS FROM SUGARCANE WASTE SOIL - E. SIRISHA; A. NAVEEN; V. BHARGHAV; M. LAKSHMI NARASU (The Bioscan, 2010)
Intracellular α-galactosidase (EC 3.2.1.22) producing bacteria were isolated from soil. The isolates were grown on the growth media with sucrose as inducer. The isolate showing maximum activity was identified by following Bergey’s manual. Different media parameters were optimized for enhanced enzyme production. α- galactosidase activity was optimal at 36ºC and pH 7.0 and when raffinose and tryptone were used as carbon and nitrogen source.